Effect of Agribusiness Partnership Model and Microcredit Scheme on Market Access and Welfare of Coffee Farmers in East Java - Kartika Lestari, Putu Fajar; Muhtadi, Muhamad Ammar; Novitasari, Salwa Aulia (West Science Social and Humanities Studies, 2025)
This study examines the influence of agribusiness partnership models and microcreation schemes on market access and their implications for the welfare of coffee farmers in East Java. Using a quantitative research approach with a sample of 200 coffee farmers, data were analyzed through Structural Equation Modeling - Partial Least Squares (SEM-PLS) using SmartPLS 3.0. The results reveal that both agribusiness partnerships and microcreation schemes have a positive and significant effect on market access. Furthermore, market access was found to significantly improve farmer welfare, acting as a mediating variable between the independent variables and welfare outcomes. These findings underscore the importance of integrated rural development strategies that combine institutional collaboration, access to finance, and market facilitation. The study contributes to the understanding of sustainable agricultural development by highlighting how structured partnerships and financial inclusion can enhance market participation and economic resilience among smallholder farmers.